Android Based E-Module on Food Services Subjects for Culinary Students - Akmal, Nikmat; Putri, Yuzia Eka; Sutanti, Siti (Journal of Education Technology, 2024)
The unavailability of interactive learning media, namely e-modules, has resulted in reduced interest in learning Food Services which includes theory and practice in the Culinary Education Study Program, resulting in low learning outcomes. This research aims to develop an Android-based e-module for the Food Services subject. The research uses a 4D development model. Data collection was carried out through interviews and questionnaires. The research subjects were students and lecturers of the Culinary Education Study Program. Data were analyzed using descriptive analysis. The e-module developed consists of a front display (university logo, e-module description, guide, and start button), and a main menu (learning objectives, content, references, and evaluation). The results of the feasibility test for the e-module developed according to material experts, media experts and students were respectively 4.36 (very feasible), 4.43 (very feasible) and 4.40 (very high acceptance). This data shows that Android-based e-modules are very suitable for use as learning media. Android-based e-modules can make it easier for students to access learning materials anywhere and at any time so that students can repeat learning independently and are able to improve students' understanding of learning materials.